The Influence of the Independent Learning Curriculum and Teacher’s Performance on The Learning Outcomes of Public High School Students in Kayuagung Sub-District - Martinah, Martinah; Putra, Alhadi Yan; Indrawati, Sri Wahyuni (Yayasan Sembilan Pemuda Indonesia, 2023)
This study aims to determine the Effect of the Independent Learning Curriculum and Teacher Performance on the Learning Outcomes of State High School Students in Kayuagung District. This type of research is quantitative research with research design using expost facto research design. The sample in this study is the total of all public high school teachers in Kayuagung sub-district. consisting of 121 teachers. Data collection techniques using questionnaires. Data analysis techniques use quantitative descriptive analysis techniques, and multiple regression. The results of this study stated that 1) there was a significant influence of the Independent Curriculum on the learning achievement of State High School students in Kayuagung District; 2) there is a significant influence on teacher performance on the learning achievement of public high school students in Kayuagung sub-district; 3) there is a significant influence together with the Independent Curriculum and teacher performance on the learning achievement of State High School students in Kayuagung District.